IIT-Kanpur project to link rural areas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
IIT-Kanpur project to link rural areas, Times of India, 14 August 2002 Mumbai - A novel project, ´Digital Gangetic Plain´, is being implemented by IIT-Kanpur and MIT Media Labs Asia to provide wireless Internet telephony (WIT) to